Thymopharyngeal cyst in an adult: a case report - Bui-Nguyen, Hoang; Nshimirimana, Jean Claude; Kamaliza, Aimee Marie; Nkurunziza, Charles; Ncogoza, Isaie; Varvares, Mark A.; Shaye, David A. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
A rare case of a thymopharyngeal cyst is identified in a young woman from Rwanda, who presented with a centrally located neck mass. Thymopharyngeal cysts, remnants of embryological thymic tissue, are infrequent findings especially in adults, and their diagnosis requires high clinical suspicion. We review the clinical presentation, diagnostic workup, surgical management, and discuss the literature on this rare entity. Our case report emphasizes the importance of including thymopharyngeal cysts in the differential diagnosis of central neck masses.